Estimation of the wetting induced settlement of loess soils from the wetting soil-water characteristic curve - Chang Li; Yuhui Chen; Ke Xiang; Guoliang Dai; Weiming Gong; Shaojun Yang; Alfrendo Satyanaga; Yuan Shen Chua; Peng Gao; Qian Zhai (Scientific Reports)
Abstract Collapsible loess soils, known for their significant volume reduction upon the wetting, pose critical challenges in the geotechnical engineering. The estimation of the wetting-induced settlement is crucial for the foundation design and the determination of the negative skin friction on the pile. In this paper, a new method is proposed to estimate the wetting induced collapse from the wetting soil-water characteristic curve (SWCC) and the index properties of the loess soils. In the proposed model, both the water-entry value (WEV) and constant water content suction (ψ wc) were adopted for the quantification of the volume change with respect to the reduction in soil suction. The proposed method is verified against the experimental data from published literature. Subsequently, the ground settlement of the loess soil in the inundated condition was calculated by adopting the proposed method and comparing the results with the field measurement data. The results of study indicated that the performance of the proposed method is better than the conventional method in predicting the ground settlement by using the local code in China.